Reviews (New blackfriars, 1980)
Book reviewed in this article: PSALM 23: AN ANTHOLOGY, compiled by K. H. Strange and R. G. E. Sandbach. HEAVEN IN ORDINARIE by Dermot O'Donoghue. T. and T. Clark GURUS, ASHRAMS AND CHRISTIANS by Vandana. D.L.T. RETURN TO THE CENTRE by Bede Griffiths. UNSEEN WARFARE, trans. E. Kadloubovsky and G. E. H Palmer. THEOLOGY ON DOVER BEACH by Nichda Lash THE NATURE OF MAN by Don Cupitt A HIDDEN REVOLUTION. The Pharisees' Search for the Kingdom Within by Ellis Rivkin CE QUE CROYAIT DOMINIQUE by P. R. Regamey